Longitudinal Strain by Speckle Tracking during Dobutamine Stress Echocardiography in Suspected Coronary Arteries Disease - Potashev, S. V.; Salo, S. V.; Gavrylyshyn, A. Y.; Hrubyak, L. M.; Unitska, O. M.; Fedkiv, S. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Speckle tracking echocardiography (STE) provides valuable information about global and regional myocardial function. STE during dobutamine stress-echocardiography (DSE) enables more reliable ischemia diagnosis. The aim of the study was to evaluate STE feasibility as a DSE visualization method and its accuracy compared to coronary angiography (CAG) in the patients with moderate-to-high coronary arteries disease (CAD) risk. Methods. We prospectively examined 140 patients (84 [60.0%] men and 56 [40.0%] women) with suspected CAD in order to verify diagnosis and evaluate myocardial viability and coronary reserve. Results. Mean left ventricular ejection fraction (LVEF) was 54.4±15.8%. All the patients had normal blood pressure (BP) and heart rate (HR) during the test. There were no significant hemodynamics alterations during the test. There were no significant complications during DSE with only 15 (12.9%) cases of different relatively low grade supraventricular and ventricular arrhythmia, mainly transitory without interventions. There were 116 (82.9%) positive DSE results, of which 2 (1.72%) were false-positive. In 2 (8.3%) patients with negative DSE results, CAG revealed 1-vessel insignificant (50– 70%) lesions with developed collaterals (false-negative results). According to DSE and CAG results, 96 (82.3%) patients underwent revascularization interventions: 86 (89.6%) percutaneous coronary interventions (PCIs) and 10 (10.4%) coronary artery bypass grafting (CABG) surgery. Sensitivity and specificity of DSE with STE for primary CAD diagnosis according to the “golden standard” CAG results were 98.3% and 91.7%, respectively, with identical positive and negative predictive values and very high overall accuracy of the method (AUC = 0.98; OR = 627.0, p<0.0001). Sensitivity and specificity of DSE with STE for defining indications for intervention and revascularization were 97.9% and 91.7%, respectively, with high overall accuracy (AUC = 0.95; OR = 564.0, p<0.0001). Combined quantification of ΔGLS and ΔWMSI for primary CAD diagnosis showed significantly lower sensitivity 86.2%(p=0.0002)andspecificity80.4%(p=0.0064)withsignificantlylowerintegralmethodaccuracy(AUC0.83,p<0.0001). Conclusions. DSE with STE as a visualization method is a safe and optimal method for ischemia diagnosis and evaluation of myocardial viability and coronary reserve in patients with suspected CAD. Given the lower ΔGLS and ΔWMSI accuracy compared to integral DSE with STE result evaluation, as well as frequent GLS growth in significant number of patients with definite positive test result, authors recommend evaluating integral test result rather than strain value.